The Intra-organizational Antecedents of Innovation in Polish Tourism Enterprises - Zbigniew ZONTEK; Ewa LIPIANIN-ZONTEK (Communications of International Proceedings, 2021)
This paper presents an empirical analysis of internal antecedents of innovation in Polish tourism enterprises. The rationale for undertaking research in this topic is the need to fill the theoretical and empirical gap in research on innovations in tourism enterprises, and their managerial aspects. Taking into consideration this cognitive gap arose following research problems: What are the sources of innovation in tourism enterprises? Do managers perceive antecedents of innovation in internal factors? The scientific goal of the study is to identify factors affecting the formation of innovation in the tourism enterprises and the impact of internal environment components on the innovation.  The primary, quantitative research presented in the paper was conducted in Poland. A representative research sample of 1200 tourism enterprises was selected to study, extracted from the population of over 12000 units placed in national databases. The presented results indicate that the impact of endogenous factors is varied, and the relatively largest impact was noted in the case of: knowledge transfer within the enterprise, efficient human resources management, creativity of employees and the creation of new knowledge resources in the company. The researched enterprises perceive human resources more through the prism of operational activity than in terms of innovation processes. They pay significant attention to the quality of human resources and personal characteristics conducive to innovation.
Keywords: Tourism Enterprise; Management; Sources of Innovation